2006
DOI: 10.1682/jrrd.2004.09.0122
|View full text |Cite
|
Sign up to set email alerts
|

Veterans Health Administration multiple sclerosis surveillance registry: The problem of case-finding from administrative databases

Abstract: Abstract-Establishment of a national multiple sclerosis (MS) surveillance registry (MSSR) is a primary goal of the Department of Veterans Affairs (VA) MS Center of Excellence. The initial query of Veterans Health Administration (VHA) databases identified 25,712 patients (labeled "VHA MS User Cohort") from fiscal years 1998 to 2002 based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code; service-connection for MS; and/or disease-modifying agent (DMA) use. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 8 publications
2
48
0
1
Order By: Relevance
“…An alternative electronic case-finding algorithm has been created in the VA that identifies a veteran as having MS if the veteran had a pharmacy record for a disease-modifying agent, evidence of MS-related service-connected disability through the Veterans Benefit Administration, or a mean of at least one inpatient or outpatient encounter each year during the time window of this study, in which the principal ICD-9-CM code was 340. 15 As a sensitivity analysis, we implemented a revised version of this algorithm (we did not have access to Veterans Benefit Administration data) and found that 5375 of the 7743 patients in this study met the definition of MS with these new criteria. The A recent systematic review suggests that the annual health-care costs for MS range from $8528 to $54,244 per patient, placing it second to congestive heart failure among chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative electronic case-finding algorithm has been created in the VA that identifies a veteran as having MS if the veteran had a pharmacy record for a disease-modifying agent, evidence of MS-related service-connected disability through the Veterans Benefit Administration, or a mean of at least one inpatient or outpatient encounter each year during the time window of this study, in which the principal ICD-9-CM code was 340. 15 As a sensitivity analysis, we implemented a revised version of this algorithm (we did not have access to Veterans Benefit Administration data) and found that 5375 of the 7743 patients in this study met the definition of MS with these new criteria. The A recent systematic review suggests that the annual health-care costs for MS range from $8528 to $54,244 per patient, placing it second to congestive heart failure among chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce inaccurate ascertainment of MS due to coding errors, we only included individuals in the final target population if they also met at least one of the following criteria at any time: (1) experienced inpatient hospitalization for MS (hospitalization coded with ICD-9-CM diagnosis code 340), (2) received a disease-modifying agent (interferon 1a, interferon 1b, or glatiramer acetate) used only to treat MS, (3) had a serviceconnected disability for MS (diagnosis confirmed through medical review for VA disability pension), or (4) had at least two outpatient encounters where the primary ICD-9-CM diagnosis code was 340 and at least one encounter where the primary ICD-9-CM diagnosis code was 340 during each year in which they received some VA medical service from FY2000 to FY2008. This algorithm for identifying an MS target population has been validated in previous work and has been shown to identify and eliminate individuals with or without MS with a high degree of sensitivity and specificity [30].…”
Section: Methodsmentioning
confidence: 99%
“…It is known that more women than men have MS [26,31] and that men with MS report more falls than do women with MS [5][6]. Veterans with MS are also younger than the general VHA population [30,32], and younger people generally fall less than older people [12,14]. We included the number of clinic visits in the model on the causal pathway between MS and falls because veterans with MS may have more clinic visits than veterans without MS, which could result in more record of injurious falls in their medical records, regardless of actual number.…”
Section: Methodsmentioning
confidence: 99%
“…From 19,311 veterans whose MS diagnosis was confirmed through application of a statistical algorithm [19], 92 cases (0.48%) were excluded because of invalid/missing zip codes, army post office or overseas zip codes, and residence outside the United States, Puerto Rico, and the Virgin Islands. The total number of VHA patients with MS used for GIS analysis in this study was 19,219.…”
Section: Study Cohortmentioning
confidence: 99%
“…A major goal of the MSCoEs is to improve the quality of and access to MS specialty care for veterans diagnosed with MS throughout the VHA system. Currently, about 39,000 veterans (VHA MS User Cohort) are seen in the VHA for MS-related issues (e.g., rule-out, diagnostic evaluation, treatment) and about 19,000 have a "confirmed" diagnosis (VHA MS Patient Cohort) [19].…”
Section: Introductionmentioning
confidence: 99%